Development of Sustainability Criteria and Indicators for Eco-Lodges and Resorts in Ecotourism Destinations: Case Studies from India - Chandran, Chindu; Bhattacharya, Prodyut (Turizam, 2022)
Ecotourism is the fastest advancing and developing market withinside the tourism enterprise and with faster progress; it’s leaving a terrible impact on the ecosystem. One of the significant stakeholders that can promote sustainability is ecotourism accommodation providers. In order to minimize their carbon footprint and negative environmental effects, many hotels and resorts around the world have launched an innovative cost-saving measures. The sustainability of a destination for ecotourism is partly dependent on the success of local eco-lodges and resorts. Certification has emerged as a strong instrument for helping to conserve natural resources and cultural heritage. The study was planned to develop performance management standard criteria and indicators (C&I) for eco-lodges and resorts in order track sustainability and current eco-tourism activities in India. The main objective is to ensure the fulfillment of the goals of ecotourism and to evaluate the working standard that is practiced in different destinations. After the stakeholder consultation, the draft standard of criteria and indicators was developed and accompanied by a comprehensive primary survey. To test the parameters of C & I, a case study review was performed across 10 prominent eco-lodges in India, which are located near ecotourism destinations. The findings of the study include the natural, social and economic aspects, along with a set of 3 principles, 5 criteria and 86 indicators to determine the sustainable functioning of eco-lodges and resorts. Best practice examples from different hotels of different sizes, ownership and locations across India are also mentioned in the paper. Such examples reflect green management initiatives that support local communities, protect natural resources and cultural practices, etc.